Long-term response and design of two geosynthetics: effect of field installation damage - Pinho-Lopes, Margarida (2020)
This paper contributes to understanding how installation damage of geosynthetics influences their long-term response and design. A geotextile and a geogrid were exhumed after installation under real conditions; their long-term tensile behaviour was investigated using conventional creep and creep rupture tests. Reduction factors for installation damage, creep and their combined effect were computed. The main aim of the paper was to assess how the long-term response of the geosynthetics was influenced by installation damage and whether it would be necessary to update current design approaches. The installation damage affected the mechanical response of both geosynthetics; important strength reductions were observed, particularly for the most severe installation conditions. The results indicate that, contrary to what has been reported in the literature, the creep rupture response of the geotextile changed after installation damage. When tested under similar creep loads (fraction of the sample tensile strength), both geosynthetics exhibited reduced potential for creep rupture and smaller strains at the end of primary creep. Changes in stiffness were less important than those for strength, for both short- and long-term response. There was synergy between installation damage and creep; the traditional approach to design was unsafe for the geotextile and slightly conservative for the geogrid.